THE IMPROVEMENT OF AUDIO-VISUAL BASED DANCE APPRECIATION LEARNING AMONG PRIMARY TEACHER EDUCATION STUDENTS OF MAKASSAR STATE UNIVERSITY - -, Wahira (Harmonia: Journal of Arts Research and Education, 2014)
This research aimed to improve the skill in appreciating dances owned by the students of Primary Teacher Education of Makassar State University, to improve the perception towards audio-visual based art appreciation, to increase the students’ interest in audio-visual based art education subject, and to increase the students’ responses to the subject. This research was classroom action research using the research design created by Kemmis & MC. Taggart, which was conducted to 42 students of Primary Teacher Education of Makassar State University. The data collection was conducted using observation, questionnaire, and interview. The techniques of data analysis applied in this research were descriptive qualitative and quantitative. The results of this research were: (1) the students’ achievement in audio-visual based dance appreciation improved: precycle 33,33%,  cycle I  42,85% and cycle II 83,33%, (2) the students’ perception towards the audio-visual based dance appreciation improved: cycle I 59,52%, and cycle II 71,42%. The students’ perception towards the subject obtained through structured interview in cycle I and II was 69,83% in a high category, (3) the interest of the students in the art education subject, especially audio-visual based dance appreciation, increased: cycle I 52,38% and cycle II 64,28%, and the students’ interest in the subject obtained through structured interview was 69,50 % in a high category. (3) the students’ response to audio-visual based dance appreciation  increased: cycle I 54,76% and cycle II 69,04% in a good category.